Chemo-physical concentration of a Low-grade nickel laterite ore. (15th March 2022) - Asadrokht, Mohammad; Zakeri, Alireza
Highlights: A novel method for the beneficiation of limonitic Ni laterites. Long-term oxalic acid leaching of a low-grade Ni laterite ore from Iran. A dissolution-precipitation behavior for Ni in contrast to leachability of Fe. Fast dissolution for Ni and Fe but delayed precipitation for Ni at high temperature. Collection of nickel oxalate particles in the fine fraction of the leach residue. Abstract: Extraction of nickel from laterites is a challenging task due to the lack of an efficient nickel concentration method. Current efforts on the beneficiation of nickel laterites–especially low-grade ones– are mainly focused on atmospheric leaching methods using mineral acids, organic acids, or a mixture of them. The aim of the present paper is developing a novel hydrometallurgical approach to concentrate nickel from laterites based on a long-term oxalic acid leaching followed by size separation of the leach residue. A limonitic laterite sample from Sarchahan deposit (Fars province, Iran) containing 0.8% Ni and 27.3% Fe was used for the experiment and dissolution behavior of nickel and iron during the course of long time leaching runs (52 h) was studied under the influence of temperature (60–90 °C) and oxalic acid concentration (0.75–1.25 M). The results show that nickel initially dissolves, but subsequently precipitates with the presence of oxalate ions as NiC2 O4 ·2H2 O. In addition, iron steadily dissolves as ferric oxalate and maintained in solution so long as light-protected. However, it tends to precipitate as FeC2 O4 ·2H2 O at higher temperatures and long retention times. The leach residue was separated into a fine and a coarse fraction via wet classification using a cut point of 44 μm. Phase and chemical analysis confirmed accumulation of nickel in the fine fraction yielding a Ni concentrate as an intermediate product. The concentrate obtained at 60 °C and 1.25 M oxalic acid concentration contained 3.2% Ni (∼10% NiC2 O4 ·2H2 O) and 3.5% Fe with a corresponding concentration ratio of 4.05, enrichment ratio of 3.44 and nickel recovery of 84%. The proposed method appears to provide a promising prospect for exploiting low-grade nickel laterites, as the obtained concentrate could be a suitable feedstock for both pyro- and hydrometallurgical processing to yield a marketable Ni product.